The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1002/cber.19831160526
|View full text |Cite
|
Sign up to set email alerts
|

Beiträge zur 15 N‐NMR‐Spektroskopie Protonierung und Tautomerie in Purinen: Purin und 7‐ und 9‐Methylpurin

Abstract: Die 15N‐NMR‐Spektren von Purin (1), 7‐ und 9‐Methylpurin (2, 3) wurden in verschiedenen Medien (NaOH, H2O, 20% H2SO4, 90% H2SO4, DMSO, CF3CO2H, FSO3H) gemessen und zugeordnet. Aus den σ(15N)‐Daten werden Protonierungsorte und Tautomerie‐Verhältnisse abgeleitet. Der Einfluß der N‐Protonierung auf die geminalen 15N, 1H‐Spin‐Spin‐Kopplungskonstanten wird diskutiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A detailed NMR study based on longrange 13 C-1 H coupling constants 33 came to the conclusion that in neutral aqueous solutions the N-7(H) : N-9(H) tautomer ratio is 1 : 1 (48 : 52), whereas in DMSO the N-9(H) tautomer is favoured by a factor of 2 (30 : 70). A similar result, with an N-7(H) : N-9(H) tautomer ratio of 35 : 65 in DMSO, was reported from a 15 N NMR study, 34 where the (experimentally not available) chemical shifts of the two tautomers, which contribute to the coalescing signals, were estimated from appropriate model compounds (7-and 9-methylpurine).…”
Section: Tautomerism Of Purinementioning
confidence: 55%
“…A detailed NMR study based on longrange 13 C-1 H coupling constants 33 came to the conclusion that in neutral aqueous solutions the N-7(H) : N-9(H) tautomer ratio is 1 : 1 (48 : 52), whereas in DMSO the N-9(H) tautomer is favoured by a factor of 2 (30 : 70). A similar result, with an N-7(H) : N-9(H) tautomer ratio of 35 : 65 in DMSO, was reported from a 15 N NMR study, 34 where the (experimentally not available) chemical shifts of the two tautomers, which contribute to the coalescing signals, were estimated from appropriate model compounds (7-and 9-methylpurine).…”
Section: Tautomerism Of Purinementioning
confidence: 55%
“…They recognized that the three-bond coupling constant in the HCNC fragment is greatly reduced by replacing the N− mediator unit with −NH−. Since then, analysis of 3 J H−C has been used several times to determine the structures of individual tautomers in purine derivatives and analogues. , Further, it has been demonstrated that the two-bond coupling of a proton to the pyrrole-type nitrogen ( 1 H−C− 15 NR−) is reduced relative to that involving the pyrimidine-type nitrogen ( 1 H−C 15 N−) . However, the contributions to the coupling pathways that derive from the electron distribution within the heterocyclic system remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The N(7)H tautomer is dominant in the solid state . In aqueous solution purine exists as an approximately equal mixture of the N(7)H and N(9)H forms. Recent experimental resonance Raman studies suggest that the N(7)H form is predominant in water while theory seems to indicate a small predominance of the N(9)H form (52%) . In DMSO the N(9)H form is preferred (70%) 11,13 and in gas phase the N(9)H tautomer is dominant.…”
Section: Introductionmentioning
confidence: 99%